2021
DOI: 10.1186/s12872-021-02251-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep habits on acute myocardial infarction risk and severity of coronary artery disease in Chinese population

Abstract: Background Growing evidence indicates that poor sleep harms health. Early to bed and early to rise is considered as a healthy lifestyle in Chinese population. The current study aimed to examine the effects of sleep habits on acute myocardial infarction (AMI) risk and severity of coronary artery disease (CAD) in Chinese population from two centers. Methods A total of 873 patients including 314 AMI cases and 559 controls were recruited from the inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Our study showed that regardless of age, insomniacs are associated with a higher risk of MI. Lian et al 32 cross‐sectional study reinforce our findings; they concluded that short sleep duration is associated with a higher risk of MI in patients <65 and >65 years old. Older age is usually associated with a higher risk of MI 33 ; this is supported by the findings in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that regardless of age, insomniacs are associated with a higher risk of MI. Lian et al 32 cross‐sectional study reinforce our findings; they concluded that short sleep duration is associated with a higher risk of MI in patients <65 and >65 years old. Older age is usually associated with a higher risk of MI 33 ; this is supported by the findings in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, short sleep duration was associated with several cardiovascular risk factors, such as type 2 diabetes and overweight (48-50). Evidence obtained by the meta-analyses of the observational studies further confirmed that short sleep duration may be an independent risk factor for CHD, all-cause and cardiovascular mortalities (51)(52)(53)(54). As for Meta-analysis results for the association between per hour longer sleep duration and CVDs in MR studies.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, short sleep duration has been linked to various cardiovascular risk factors, including type 2 diabetes and overweight (43)(44)(45)(46). Moreover, meta-analyses of observational studies have further confirmed that short sleep duration could serve as an independent risk factor for CHD and is associated with higher risks of all-cause and cardiovascular mortalities (47)(48)(49). Regarding stroke, observational studies have suggested that short sleep duration is associated with an elevated risk of stroke (50)(51)(52)(53), and a meta-analysis of such studies further substantiated this finding (54).…”
Section: Discussionmentioning
confidence: 95%